THE CONSTRUCTION OF A NEW MATHEMATICAL MODEL FOR ISLAMIC HOME FINANCING - Puspa Liza Ghazali,; Sharifah Arni Syed Jaaffar,; Nik Hazimi Mohammed Foziah,; Abdul Malek A Tambi,; Farah Amalina Md Nawi,; Mustafa Mamat,; Saiful Bahri Mohammad,; Wan Mohd Nazri Wan Daud,; Mohd Sadad Mahmud, (Asian Academy of Management Journal, 2019)
Islamic financial institutions apply few mathematical formulas in constructing Islamic home financing models. However, the available products in the markets are deemed to be a burden to the low to medium income earners, while the mortgage takaful only compensates selected cases such as death and total permanent disability without including the protection against those who loss an effort to work. Hence, this study derives a new formula of Islamic home financing where the profit is calculated based on one-third of the total amount of financing, while the new model of mortgage takaful will compensate those who are losing effort to work. Therefore, this study aims to derive a new formula of home financing and mortgage takaful model by using an integrated model.